State Violence in Mapuche Territory: The Death of Alex Lemün and the Fight for Justice in Chile (2002-2022); [Violência Estatal No Território Mapuche: A Morte de Alex Lemün E a Luta por Justiça No Chile (2002-2022)]; [Violencia de Estado en Territorio Mapuche: La Muerte de Alex Lemün y la Lucha por la Justicia en Chile (2002-2022)] - Canales-Tapia, P (Universidade Estadual de Ponta Grossa, Editora, 2025)
This paper deals in a historical way, the murder – in a rural context – of the young Mapuche Alex Lemün, struck by police bullets in November 2022 in the province of Malleco, in the Araucanía region. His death is a reflection of sustained and systematic racist and violent state behavior against the Mapuche people and their historical demands. Theoretically, this work is articulated from the debates around racialized violence and racial hate speech, as a colonial trend not overcome by the Chilean state. Methodologically, this work is based on criticism and diversity of sources and their analysis, based on the analysis of the discourse and its implications. © 2025 Universidade Estadual de Ponta Grossa, Editora. All rights reserved.